2010
DOI: 10.1016/j.urology.2009.06.112
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Clinical Outcomes of a Phase I Trial of Intravesical Docetaxel in the Management of Non–muscle-invasive Bladder Cancer Refractory to Standard Intravesical Therapy

Abstract: OBJECTIVES To report the long-term clinical outcomes and durability of response after treatment with induction intravesical docetaxel. Most novel agents used to treat bacillus Calmette-Guerin refractory high-grade non–muscle-invasive (NMI) bladder cancer are evaluated only after short follow-up periods. Our previously published phase I trial demonstrated that docetaxel is a safe agent for intravesical therapy with minimal toxicity and no detectable systemic absorption. We sought to determine long-term clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 12 publications
1
30
0
Order By: Relevance
“…Laudano et al [23] reported the clinical outcomes of a phase I trial of intravesical use of docetaxel as 6 weeks induction therapy in patients with at least one course of failed BCG therapy. Of 18 patients, 4 patients had demonstrated complete, and 3 patients partial responses; whereas 11 patients had failed treatment without significant toxicity after a median follow-up of 48.3 months.…”
Section: Taxanesmentioning
confidence: 99%
“…Laudano et al [23] reported the clinical outcomes of a phase I trial of intravesical use of docetaxel as 6 weeks induction therapy in patients with at least one course of failed BCG therapy. Of 18 patients, 4 patients had demonstrated complete, and 3 patients partial responses; whereas 11 patients had failed treatment without significant toxicity after a median follow-up of 48.3 months.…”
Section: Taxanesmentioning
confidence: 99%
“…6,9,117 Long-term clinical outcomes in this cohort revealed 22% and 17% complete and partial response rates, respectively, while 61% failed treatment at a median follow-up of 48.3 months. 118 In a recent update of their series of 33 patients with refractory NMIBC, Barlow et al reported a 61% complete response rate after six weeks of induction therapy, and one-and two-year recurrence-free survival rates were 45% and 32%, respectively. 119 Taxoids are attractive candidates for intravesical therapy due to their potency, high molecular …”
Section: Apaziquonementioning
confidence: 99%
“…Other combinations of intravesical agents are currently being evaluated. 42,43 Some patients that are candidates for cystectomy are not suitable for radical surgery because of the presence of comorbid medical illnesses or because they refuse surgery even after extended discussion of the risks. In these circumstances, alternative strategies are available but with a guarded success rate.…”
Section: Recurrent Diseasementioning
confidence: 99%